TOKCER BANTALAN : Tongkat Cerdas Alat Bantu Jalan Penyandang Tunanetra Menggunakan Arduino Mega 2560 dengan Sensor Ultrasonic HC SR-04 dan Water Level - Ririn Solekha; Maimun Zaki; Laila Aida Fatimah; Rahmat Hidayat (Jurnal Komputer dan Elektro Sains, 2023)
Technology can be used in various fields that can support research, of course the results of this research can be useful and beneficial as a form of community service. Even today, technology plays a role in helping people with special needs (disabilities) experience difficulties. . One example is blind people who experience difficulties due to limited vision so that sticks are used as a solution to be used as walking aids for people with disabilities in facilitating their daily activities. Therefore, the authors designed a tool called "TOKCER BANTALAN : A Smart Stick for the Blind Auxiliary Tool" with the research method being carried out starting from the stage of conducting a literature study which is a process of reviewing the literature on references related to the research being carried out. . After that, preparation includes technical and non-technical aspects such as basic preparation related to hardware devices, software tools that support research. Then proceed with the process of testing the tools including the program and analysis of the results of the research conducted. The results of this study are walking aids for the blind using the Arduino Mega 2560 microcontroller equipped with an ultrasonic sensor HC-SR 04 that can detect distances < 50 cm, a water level sensor that can detect standing water with a distance of ≤ 40 mm, and is equipped with a panel solar power as input power to be able to run the tool. In addition, this tool will automatically issue sound notifications when it detects objects and puddles blocking the way for the blind. It is hoped that this research will make it easier for the blind to carry out daily activities